THE PRESENT DAY RHEOLOGY, STRESS FIELD AND DEFORMATION ALONG THE DSS PROFILE FENNIA IN THE CENTRAL FENNOSCANDIAN SHIELD - Moisio K.; Kaikkonen P. (My University, 2004)
The calculation of the rheological structure in the deep seismic profile FENNIA in the central Fennoscandian Shield allows in addition the modelling of the present-day stress field and state of deformation. Seismic and surface heat flow data together with all other applicable information are used in the construction of the model. Derivation of the two-dimensional rheological structure requires the determination of the temperature field and the use of known rheological laws both for the brittle and the ductile mechanisms. The rheological model is furthermore subjected to compressional loading resulting in the structural model, which is solved as well as the thermal model by the finite-element method. Results show that rheologically weak crustal layers can be generated under suitable conditions in the central Fennoscandian Shield. These are more evident when assuming wet conditions for the upper and middle crust. Although these weak layers are found the application of the rheological structure to a model, where stress and deformation are derived does not generate intensive crustal deformation. In the stress field influence of the rheology is very small in the crustal part whereas in the mantle a clear effect is seen at the depth of 100km where plastic deformation begins. Uncertainties related to thermal modelling and how these affect rheological and structural modelling are also analysed in a quantitative form showing the importance of temperature in tectonic modelling.